Association of Acetaminophen and Ibuprofen Use With Wheezing in Children With Acute Febrile Illness. (March 2017) - Matok, Ilan; Elizur, Arnon; Perlman, Amichai; Ganor, Shani; Levine, Hagai; Kozer, Eran
Background: Many infants and children receive acetaminophen and/or ibuprofen during febrile illness. Previously, some studies have linked acetaminophen and ibuprofen use to wheezing and exacerbation of asthma symptoms in infants and children.Objective: To assess whether acetaminophen or ibuprofen use are associated with wheezing in children presenting to the emergency department (ED) with febrile illness.Methods: This was a cross-sectional study of children who presented with fever to the pediatric ED between 2009 and 2013. The data were collected from questionnaires and from the children's medical files. Patients with wheezing in the ED were compared with nonwheezing patients. Associations between medication use and wheezing were assessed using univariate and multivariate analyses. The multivariate analysis adjusted for potential confounding variables (ie, age, atopic dermatitis, allergies, smoking, antibiotics use, etc) via propensity scores.Results: During the study period, 534 children admitted to the ED met our inclusion criteria, of whom 347 (65%) were included in the study. The use of acetaminophen was similar in children diagnosed with wheezing compared with those without wheezing (n = 39, 81.3%, vs n = 229, 82.7%, respectively). Ibuprofen use was significantly lower in children diagnosed with wheezing (n = 22, 52.4%, vs n = 168, 69.4%, respectively). In multivariate analysis, acetaminophen was not associated with a higher rate of wheezing during acute febrile illness (adjusted odds ratio [OR] = 0.76, 95% CI = 0.24- 2.39), whereas ibuprofen was associated with a lower risk of wheezing (adjusted OR = 0.36, 95% CI = 0.13-0.96).Conclusions: Our study suggests that acetaminophen and ibuprofen are not associated with increased risk for wheezing during acute febrile illness.